Detection of high‐risk human papillomaviruses in fresh breast cancer samples using the hybrid capture 2 assay. Issue 12 (19th August 2013) - Liang, Weili; Wang, Jianli; Wang, Chongjie; Lv, Yanrong; Gao, Haidong; Zhang, Kai; Liu, Huantao; Feng, Jinbo; Wang, Leiyi; Ma, Rong
Abstract The etiology of breast cancer remains unknown and the role of human papillomavirus (HPV) in breast carcinogenesis is controversial. This study investigated the prevalence of high‐risk HPV infections in Chinese women with breast cancer and the possible relationship between high‐risk HPV infection and the clinicopathological characteristics of breast cancer. Tumor cells from 224 fresh breast cancer samples and 37 fresh breast fibroadenomas were collected for hybrid capture 2 (HC2) assay. HC2 was the only technique approved by the United States Food and Drug Administration for screening for high‐risk HPV infection in 2008. The prevalence of high‐risk HPV infection in breast cancer samples was 21.4%, which was slightly higher than the 16.2% observed in breast fibroadenomas. Age and menopausal status were not risk factors for high‐risk HPV infection among breast cancer patients. The clinical and pathological characteristics of breast cancer showed no significant correlation with high‐risk HPV infection. Although the prevalence of 13 subtypes of high‐risk HPV infections was similar in breast cancer and nonmalignant breast samples, the presence of high‐risk HPVs in both malignant and benign breast samples implies that a possible causal role in breast cancer carcinogenesis could not be ruled out. Clarifying the possible link between high‐risk HPVs and breast cancer might benefit women vaccinated against HPV and could decrease the incidence of HPV‐related breast cancer. J. Med. Virol. 85:2087–2092, 2013. © 2013 Wiley Periodicals, Inc.